Molecular Biology : Structure and Dynamics - Walker, Edward (United States : Murphy & Moore Publishing, 2022)
The branch of biology which is concerned with the study of biological activity in and between cells at a molecular level is known as molecular biology. Areas of focus under this discipline are synthesis and functions of DNA, RNA and other essential proteins. The guiding principles of molecular biology are the processes which govern how DNA is transcribed into RNA and finally translated into proteins. This field is closely related to the subjects of biochemistry and genetics. Some prominent methods used in molecular biology to study the structures of proteins are molecular cloning, gel electrophoresis, polymerase chain reaction, microarrays, allele specific oligonucleotide, macromolecule blotting and probing. This book is compiled in such a manner, that it will provide in-depth knowledge about the theory and practice of molecular biology. While understanding the long-term perspectives of the topics, it makes an effort in highlighting their impact as a modern tool for the growth of the discipline. This book aims to serve as a resource guide for students and experts alike and contribute to the growth of the discipline.
Includes index.
Includes bibliographical references.
Keywords: Molecular biology; Biochemistry; Gene therapy